CONTAMINAÇÃO POR Hg, Pb E CN- GERADA PELA GARIMPAGEM DE OURO SOBRE OS RIOS SUCIO, MICO E SINECAPA, NICARÁGUA, AMÉRICA CENTRAL - Velásquez, G. A. S.; Fenzl, N.; Guillen, S. M.; Nascimento, F. (Geochimica Brasiliensis, 2011)